Mechanisms and Treatment of Halogen Inhalation–Induced Pulmonary and Systemic Injuries in Pregnant Mice. Issue 2 (August 2017) - Lambert, James A.; Carlisle, Matthew A.; Lam, Adam; Aggarwal, Saurabh; Doran, Stephen; Ren, Changchun; Bradley, Wayne E.; Dell'Italia, Louis; Ambalavanan, Namasivayam; Ford, David A.; Patel, Rakesh P.; Jilling, Tamas; et al.
Abstract : Inhalation of oxidant gases has been implicated in adverse outcomes in pregnancy, but animal models to address mechanisms and studies to identify potential pregnancy-specific therapies are lacking. Herein, we show that inhalation of bromine at 600 parts per million for 30 minutes by pregnant mice on the 15th day of embryonic development results in significantly lower survival after 96 hours than an identical level of exposure in nonpregnant mice. On the 19th embryonic day, bromine-exposed pregnant mice have increased systemic blood pressure, abnormal placental development, severe fetal growth restriction, systemic inflammation, increased levels of circulating antiangiogenic short fms-like tyrosine kinase-1, and evidence of pulmonary and cardiac injury. Treatment with tadalafil, an inhibitor of type 5 phosphodiesterase, by oral gavage 1 hour post-exposure and then once daily thereafter, attenuated systemic blood pressures, decreased inflammation, ameliorated pulmonary and cardiac injury, and improved maternal survival (from 36% to 80%) and fetal growth. These pathological changes resemble those seen in preeclampsia. Nonpregnant mice did not exhibit any of these pathological changes and were not affected by tadalafil. These findings suggest that pregnant women exposed to bromine may require particular attention and monitoring for signs of preeclampsia-like symptoms. Abstract : Supplemental Digital Content is available in the text.